257 Effect of the Essential Amino Acid-Nitrogen to Total Nitrogen Ratio on Lysine Requirement for Nitrogen Retention in Growing Pigs. (21st September 2022) - Camire, Carley; Rodrigues, Lucas Alves; Panisson, Josiane C; Shoveller, Anna-Kate; Columbus, Daniel A
Abstract: Low-protein (LP) diets may become limiting in nitrogen (N), affecting utilization of essential amino acids (EAA) for nitrogen retention (NR). The objective of the present study was to determine the effect of the EAA-N to total N ratio (EAA-N:TN) on lysine (Lys) requirement for NR. A total of 80 growing barrows (21.5±0.89 kg initial BW) were randomly assigned to 1 of 10 dietary treatments (n=8 pigs/treatment) in 8 blocks in a 2 × 5 factorial arrangement with factors of EAA-N:TN (low vs. high) and Lys content (0.82, 0.92, 1.02, 1.12, and 1.22% standardized ileal digestible [SID] Lys). Diets were formulated to meet EAA requirements with the low ratio diet (LR; 16.8% crude protein) having an ideal EAA-N:TN of 0.48 and the high ratio diet (HR; 15.5% crude protein) formulated to be limiting in NEAA with an EAA-N:TN of 0.55. Diets were fed at 2.8 × maintenance metabolizable energy requirements. After a 7-d dietary adaptation, a 4-d N-balance period was conducted where fresh fecal samples were collected daily and quantitative urine samples were collected over a 24-h period. Nitrogen-balance was determined as the difference between N intake minus fecal and urinary N output. Data were analyzed using a MIXED model with fixed effects of ratio, Lys, and their interactions, and block as a random effect. Lysine requirement based on two-phase linear or quadratic modeling was estimated using PROC NLIN. Nitrogen retention increased linearly with increasing Lys levels regardless of ratio (P< 0.01). Quadratic modelling estimated the Lys requirement to maximize NR at 17.83 g/d in pigs fed HR diets at 1.21% SID (R 2 = 0.53; P< 0.05), but no breakpoint was achieved for pigs fed LR diets, which showed a linear response (R 2 = 0.79; P< 0.05). These results suggest that NR is limited by NEAA or TN in HR diets.